PERIOPERATIVE NURSING EDUCATION IN CANADA: CURRENT AND FUTURE PERSPECTIVES - Page-Cutrara, Karin (Operating Room Nurses Association of Canada Journal, 2007)
Current nursing issues such as the nursing shortage, recent changes to basic nursing education, and ongoing fiscal restraints have had consequences for operating room nursing education. The purpose of this article is to discuss approaches for lessening the negative effects that current nursing issues may have on perioperative nursing education in Canada. The delivery of this specialty education should be reviewed to determine if it is fully addressing the issues facing the nursing profession as a whole. The resulting negative impact on recruitment and retention in perioperative programs, on generalist and specialty training, and on funding levels require careful examination and supportive solutions. Establishing the best responses to these challenges will require further discussion of perioperative nursing education delivery.